A Combined “Hanging Liver Maneuver” and “Intrahepatic Extra-Glissonian Approach” for Anatomical Right Hepatectomy: Technique Standardization, Results, and Correlation With Portal Pedicle Anatomy - Makdissi, Fabio Ferrari; Mattos, Bruno Vinicius Hortences de; Kruger, Jaime Arthur Pirola; Jeismann, Vagner Birk; Coelho, Fabricio Ferreira; Herman, Paulo (Frontiers in Surgery, 2021)
Background: The hanging liver maneuver and intrahepatic extra-Glissonian approach are distinct modalities to facilitate safe anatomical liver resections. This study reports a standardized combination of these techniques focusing on safety, results and correlation with portal pedicle anatomy in oncological patients. Method: Combined hanging liver maneuver and intrahepatic extra-Glissonian approach for anatomic right hepatectomy was described stepwise. Portal pedicle anatomy was correlated with the Glissonian approach failure and complications. Clinical characteristics of patients, perioperative outcomes, short and long-term survival rates were analyzed. Results: Thirty colorectal liver metastases patients submitted to the combined approach were evaluated. Anatomical variations of the right portal pedicle were present in 26.6%. Hanging liver maneuver was feasible in 100%, and Glissonian approach in 96.7% despite portal pedicle variations. Mean operative time was 326 minutes. Mean blood loss was 507 ml. Mean hospital stay was 8 days. There was no 90-day operative mortality and no significant morbidity. Oncological surgical margins were free. Overall and disease-free 5-year survival were 59% and 37%. Conclusion: Regardless of frequent anatomical variations of the right portal pedicle, the hanging liver maneuver and intrahepatic extra-Glissonian approach can be combined, being useful for anatomical right hepatectomies in a safe and reproducible way in most patients.